Fiscal Stabilization in the United States: Lessons for Monetary Unions - Plamen Nikolov; Paolo Pasimeni (Bank of Finland, 2019)
The debate about the use of fiscal instruments for macroeconomic stabilization has regained prominence in the aftermath of the Great Recession, and the experience of a monetary union equipped with fiscal shock absorbers, such as the United States, has often been a reference. This paper enhances our knowledge about the degree of macroeconomic stabilization achieved in the United States through the federal budget, providing a detailed breakdown of the different channels. In particular, we investigate the relative importance and stabilization impact of the federal system of unemployment benefits and of its extension as a response to the Great Recession. The analysis shows that in the United States, corporate income taxes collected at the federal level are the single-most efficient instrument for providing stabilization, given that even with a smaller size than other instruments they can provide important effects, mainly against common shocks. On the other hand, Social Security benefits and personal income taxes have a greater role in stabilizing asymmetric shocks. A federal system of unemployment insurance, then, can play an important stabilization role, in particular when enhanced by a discretionary program of extended benefits in the event of a large shock, like the Great Recession.
URN:NBN:fi:bof-201909121461
Keywords: E63; F36; F41; F45; 330; Monetary Union; Macroeconomic Stabilization; Fiscal Policy; Monetary Policy